Research on Control Method of Pollutant Total Amount of Water Quality based on Fuzzy Mathematics - Liu, Rui (Earth Sciences Research Journal, 2020)
With the increase of pollutants discharged into the water, it is difficult to control the water environment pollution via reducing part of pollutant discharge. Therefore, the control method of pollutant total amount of water quality based on fuzzy mathematics is proposed. Firstly, a control framework and process of the pollutant total amount was built. The total amount of pollutant discharged into this region was controlled within a certain amount to achieve the predetermined environmental objective. Then, water pollution of different regions was evaluated via water quality model based on the fuzzy mathematics in the region or key protection domain with severe pollution and a concentrated pollution source, which makes the comprehensive evaluation of the water quality pollution more scientific. Finally, the control of pollutant total amount was completed via the optimized combination of point source control and unit control of total amount. Experimental results show that the method is scientific, objective and reasonable during controlling the pollutant discharge. It controls the pollutant total amount excellently.